IMPROVING MATHEMATICAL PROBLEM SOLVING BY IMPLEMENTING TEAMS GAMES TOURNAMENT MODEL ON SIMILAR TRIANGLES TOPIC IN IX GRADERS OF MTs NEGERI 2 MEDAN - Edy . Surya; Elvi . Khairunnisa (Universitas Negeri Medan, 2019)
ABSTRACT The aim of this research is to know the improvement of students’ mathematical problem solving ability through the implementation of Teams Games Tournament model on similar triangles topic. Type of this research is Classroom Action Research.The subjects were 35 students in IX graders. The object of this research is the ability of mathematical problem solving and the model that has been implemented is Teams Games Tournament.This research consisted of two cycles, and each cyclesconsists of two meetings. Mathematical problem solving ability was tested at the endingmeeting. The results of this research could be shown:(1)The process of implementation Teams Games Tournament was running well. (2)The average value of initial test of students' problemsolving ability is 61.50, the classical completeness is 31.43% and mathematical problem solving ability of students categorized as low, (3)The average valueofstudents' problemsolving ability test in the Cycle I is 69.43, the classical completeness is 42.86% and mathematical problem solving ability of students categorized as medium. But the gain of this cycle is 0.20, and it islower. (4) The average value ofstudents' problemsolving ability test in the Cycle IIis 79.14, the classical completeness 88.57%and mathematical problem solving ability of students categorized as medium. The gain of this cycle is 0.32, and it is medium.Finally, we concluded that the implementation of Teams Games Tournament model can improve students' problem solving ability. The recommendation to other researcher is able to usethis model as an alternative in the learning process that can improve students’ problem solving ability.Keywords: Mathematical Problem Solving,Teams Games Tournament. ABSTRAK Tujuan dari penelitianiniadalah untuk mengetahui peningkatan kemampuan pemecahan masalah matematika siswa yang dilakukan dengan mengimplementasikan model Teams Games Tournament (TGT) pada topik kesebangunan segitiga. Tipe penelitian ini adalah Penelitian Tindakan Kelas (PTK).Subjek dari penelitian ini adalah siswa kelas IX yang berjumlah 35 siswa. Objek dari penelitian ini adalah kemampuan pemecahan masalah matematika siswa dan model yang digunakan adalah Teams Games Tournament (TGT).Penelitian ini terdiri dari dua siklus, dan setiap siklus terdiri dari dua pertemuan. Kemampuan pemecahan masalah matematika telah dilakukan tes pada setiap akhir pertemuan. Hasil dari penelitian ini menunjukkan: (1) Proses pengimplementasian Teams Games Tournament (TGT) berjalan dengan baik,(2) Rata- rata nilai tes awal kemampuan pemecahan masalah matematika siswa adalah 61.50, ketuntasan klasikal 31.43% dan kemampuan pemecahan masalah matematika siswa dikategorikan rendah, (3)Rata- rata nilai tes kemampuan pemecahan masalah matematika siswa pada Siklus I adalah 69.43, ketuntasan klasikal 42.86% dan kemampuan pemecahan masalah matematika siswa dikategorikan menengah. Nilai gain pada siklus ini adalah 0.20, dan masih rendah, (4) Rata- rata nilai tes kemampuan pemecahan masalah matematika siswa pada Siklus II adalah 79.14, ketuntasan klasikal 88.57% dan kemampuan pemecahan masalah matematika siswa dikategorikan menengah. Nilai gain pada siklus ini adalah 0.32, dan sudah dikategorikan menengah.Sehingga, dapat simpulkan bahwa pengimplementasian model Teams Games Tournament (TGT) dapat meningkatkan kemampuan pemecahan masalah matematika siswa. Rekomendasi kepada peneliti yang lain agar dapat menggunakan model ini sebagai alternatif dalam kegiatan pembelajaran yang dapat meningkatkan kemampuan pemecahan masalah matematika siswa.Keywords: Mathematical Problem Solving,Teams Games Tournament (TGT).